Robustness of hypofractionated breast radiotherapy after breast-conserving surgery with free breathing - Chen, Kunzhi; Sun, Wuji; Han, Tao; Yan, Lei; Sun, Minghui; Xia, Wenming; Wang, Libo; Shi, Yinghua; Ge, Chao; Yang, Xu; Li, Yu; Wang, Huidong (Frontiers in Oncology, 2023)
Purpose This study aimed to evaluate the robustness with respect to the positional variations of five planning strategies in free-breathing breast hypofractionated radiotherapy (HFRT) for patients after breast-conserving surgery. Methods Twenty patients who received breast HFRT with 42.72 Gy in 16 fractions were retrospectively analyzed. Five treatment planning strategies were utilized for each patient, including 1) intensity-modulated radiation therapy (IMRT) planning (IMRTpure); 2) IMRT planning with skin flash tool extending and filling the fluence outside the skin by 2 cm (IMRTflash); 3) IMRT planning with planning target volume (PTV) extended outside the skin by 2 cm in the computed tomography dataset (IMRTePTV); 4) hybrid planning, i.e., 2 Gy/fraction three-dimensional conformal radiation therapy combined with 0.67 Gy/fraction IMRT (IMRThybrid); and 5) hybrid planning with skin flash (IMRThybrid-flash). All plans were normalized to 95% PTV receiving 100% of the prescription dose. Six additional plans were created with different isocenter shifts for each plan, which were 1 mm, 2 mm, 3 mm, 5 mm, 7 mm, and 10 mm distally in the X (left-right) and Y (anterior-posterior) directions, namely, (X,Y), to assess their robustness, and the corresponding doses were recalculated. Variation of dosimetric parameters with increasing isocenter shift was evaluated. Results All plans were clinically acceptable. In terms of robustness to isocenter shifts, the five planning strategies followed the pattern IMRTePTV, IMRThybrid-flash, IMRTflash, IMRThybrid, and IMRTpure in descending order. V95% of IMRTePTV maintained at 99.6% ± 0.3% with a (5,5) shift, which further reduced to 98.2% ± 2.0% with a (10,10) shift. IMRThybrid-flash yielded the robustness second to IMRTePTV with less risk from dose hotspots, and the corresponding V95% maintained >95% up until (5,5). Conclusion Considering the dosimetric distribution and robustness in breast radiotherapy, IMRTePTV performed best at maintaining high target coverage with increasing isocenter shift, while IMRThybrid-flash would be adequate with positional uncertainty<5 mm.